PURCHASING BEHAVIOR AND SATISFACTION OF FAST-FOOD RESTAURANT CUSTOMERS IN CALBAYOG CITY - David, Joseph Emil Ampuan; Fabillar, Herbert Manang (Jurnal Manajemen dan Kewirausahaan, 2024)
This paper examined the relationship between satisfaction and purchasing behavior of fast-food restaurant customers in Calbayog City. In addition, this study also aimed to identify the respondents' profiles and the different factors influencing their satisfaction and purchasing behavior. The researchers used a descriptive-correlational research design to conduct this study. The researchers used a structured questionnaire adopted from a previous study. The questionnaires were provided to 384 participants in Calbayog City. The gathered data were analyzed using SPSS 29. The analyzed data by the researchers showed that family members, dine-in or online order options, and restaurant menus influence the purchasing behavior of fast-food restaurant customers. On the other hand, the satisfaction of fast-food restaurant customers in Calbayog City was influenced by menu options, payment methods, online application or website navigation, food placement technology, customers’ testimonials, friends and family recommendations, and services. The study revealed no significant relationship between satisfaction and purchasing behavior of restaurant customers in Calbayog City.